Big Data: Challenges and Solutions - Srinuvasu, MA; Koushik, A; Santhosh, EB (International Journal of Computer Sciences and Engineering, 2025)
Big data is huge amount of data which is beyond the processing capacity of conventional data base systems to manage and analyze the data in a specific time interval. The data is too big to store and processed by a single machine. New innovative methods are necessary to process and store large volumes of data. This paper endows with overview of big data, its size, nature, 12Vs of Big data and some technologies to handle it